2003
DOI: 10.1051/0004-6361:20031503
|View full text |Cite
|
Sign up to set email alerts
|

The eclipsing binary star RZ Cas

Abstract: Abstract. In a first report on the results of a multi-site campaign in 2001 of photometric and spectroscopic observations of the active semi-detached Algol-type system RZ Cas, we concentrate on the radial velocity (RV) variations. Using weak absorption lines we obtain an improved orbital solution for both components. In the orbital RV curve we observe a strong, asymmetric rotation effect. For the first time we detect rapid spectroscopic multi-mode pulsations in an Algol system. Whereas the photometrically obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…Only one pulsation frequency, being about 64.19 cd −1 , had been obtained up to 2000. On the other hand, spectroscopic observations made in 2001 showed the existence of at least two close frequencies with the values of 56.6 cd −1 and 64.189 cd −1 (Lehmann & Mkrtichian 2004). …”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Only one pulsation frequency, being about 64.19 cd −1 , had been obtained up to 2000. On the other hand, spectroscopic observations made in 2001 showed the existence of at least two close frequencies with the values of 56.6 cd −1 and 64.189 cd −1 (Lehmann & Mkrtichian 2004). …”
Section: Introductionmentioning
confidence: 88%
“…d 1953 and a δ Scuti-type primary component (Ohshima et al 1998(Ohshima et al , 2001; Lehmann & Mkrtichian 2004;Rodriguez et al 2004) . The spectral types of the primary and the secondary components are A3V and K0IV, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, radial and nonradial pulsation modes detected in both, photometric and spectroscopic observations for other spectral types, indicate that a signal of 10 µmag can have a counterpart of 1 m s −1 in RVs (e.g. δ Scuti and γ Dor oscillators such as FG Vir, RZ Cas, 9-Aur, HR 8799, gam Dor, and HD 49434; Zima et al 2006;Lehmann & Mkrtichian 2004;Zerbi et al 1997Zerbi et al , 1999Krisciunas et al 1995;Uytterhoeven et al 2008); an amplitude that is detectable with HARPS-ESO, which has a reported RV precision in the short-term of 0.5 m s −1 (Lovis & Fischer 2010).…”
Section: E-mail: Zaira@iaaesmentioning
confidence: 99%
“…Also, accretion in an interacting binary might be studied via the RM effect (e.g. Lehmann & Mkrtichian 2004).…”
Section: Introductionmentioning
confidence: 99%